Training Cesarean Section: A Scoping Review. Issue 4 (August 2019) - Zetner, Diana B.; Petersen, Iben; Konge, Lars; Thinggaard, Ebbe
Abstract : Summary Statement: This study is a scoping review that reviews the existing literature on educational strategies in training of cesarean section. A systematic search was carried out in relevant databases, identifying 28 studies for inclusion. Thematic analysis revealed the following training strategies: simulation-based training (team training, in situ training, technical training), simulators (low-fidelity simulators, high-fidelity simulators), clinical training, e-learning or videos, classroom-based learning (lectures, small groups), and assessment (assessment programs/interventions, assessment of learners). Simulation-based training provides a unique milieu for training in a safe and controlled environment. Simulation-based team training is widely accepted and used in obstetrics and improves nontechnical skills, which are important in emergency cesarean section. High-fidelity simulators are advanced and realistic, but because of the expense, low-fidelity simulators may provide a reasonable method for training surgical skills. The literature in training and assessment of surgical skills in relation to cesarean section is sparse, and more studies are warranted. Abstract : Supplemental digital content is available in the text.